Maternal mycoestrogen exposure in relation to timing of birth and placental corticotropin releasing hormone concentrations in a U.S. pregnancy cohort - Alyssa Juenke; Megan C. Hansel; Carolyn W. Kinkade; Anita Brinker; Maria Bowman; Roger Smith; Richard K. Miller; Jessica Brunner; Brian Buckley; Thomas G. O’Connor; Lauren M. Aleksunes; Zorimar Rivera- Núñez; et al. (Reproductive Toxicology, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

A controlled and scalable noble gas injection method for quantitative tracer tests in hydrogeological studies - Morgan Peel; Kai Solanki; Philip Brunner; Daniel Hunkeler; Oliver S. Schilling; Rolf Kipfer (Water Research, 2026)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Metastasis-directed stereotactic radiotherapy in patients with breast cancer: results of an international multicenter cohort study - Alexander Fabian; Daniel Buergy; Fabian Weykamp; Juliane Hörner-Rieber; Denise Bernhardt; Judit Boda-Heggemann; Montserrat Pazos; Nora Mehrhof; David Kaul; Alicia S. Bicu; Eugenia Vlaskou Badra; Susanne Rogers; et al. (Clinical & Experimental Metastasis, 2025)
Metastasis-directed therapy (MDT) for oligometastatic breast cancer (≤ 5 metastases) has shown little effect in specific scenarios of randomized trials. Therefore, we aimed to assess outcomes after metastasis-directed stereotactic radiotherapy (SRT) in various clinical scenarios. We conducted an international retrospective cohort study in thirteen centers including breast cancer patients receiving SRT to any metastatic site. Outcomes included local recurrence (LR), progression-free survival (PFS), and overall survival (OS). Cumulative incidence analysis was used for LR, Kaplan–Meier estimates for PFS and OS. Covariables included patient, disease, and SRT characteristics. We performed univariable and multivariable analyses (MVA). Among 444 patients, 751 metastases were treated with SRT. Of these, 73% were intracranial and 27% extracranial lesions. Oligometastatic disease (OMD) was present in 66% of the patients. LR after two years occurred significantly more often in intracranial (25%) versus extracranial lesions (7%). In MVA of patients with OMD treated for intracranial sites, higher performance status was significantly associated with longer PFS. Further, higher performance status, biologic subtype (HR-pos./HER2-pos.), and MDT to all sites were significantly associated with longer OS. In MVA of oligometastatic patients treated for extracranial sites, biologic subtype (HR-neg./HER2-pos.) and synchronous metastasis were associated with significantly longer PFS, whereas higher grading was associated with significantly shorter PFS. Moreover, biologic subtype (HR-neg./HER2-neg.) was associated with significantly shorter OS. In conclusion, the role of MDT for breast cancer may vary per clinical scenario. Patients with OMD treated for intracranial lesions who had MDT to all sites showed superior OS. Our results should be validated prospectively.

Increasing Hydroclimatic Whiplash Can Amplify Wildfire Risk in a Warming Climate - Daniel L. Swain; John T. Abatzoglou; Christine M. Albano; Manuela I. Brunner; Noah S. Diffenbaugh; Crystal Kolden; Andreas F. Prein; Deepti Singh; Christopher B. Skinner; Thomas W. Swetnam; Danielle Touma (Global Change Biology, 2025)

Prenatal exposure to phthalates and phthalate replacements in relation to chorionic plate surface vasculature at delivery - Emily S. Barrett; David Skrill; Elaine Zhou; Sally W. Thurston; Theresa Girardi; Jessica Brunner; Hai-Wei Liang; Richard K. Miller; Carolyn M. Salafia; Thomas G. O'Connor; Jennifer J. Adibi (Science of The Total Environment, 2025)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Associations between mycoestrogen exposure and sex steroid hormone concentrations in maternal serum and cord blood in the UPSIDE pregnancy cohort - Carolyn W. Kinkade; Lauren M. Aleksunes; Anita Brinker; Brian Buckley; Jessica Brunner; Christina Wang; Richard K. Miller; Thomas G. O'Connor; Zorimar Rivera-Núñez; Emily S. Barrett (International Journal of Hygiene and Environmental Health, 2024)

Verification of the Fourier-enhanced 3D finite element Poisson solver of the gyrokinetic full-f code PICLS - A. Stier; A. Bottino; M. Boesl; M. Campos Pinto; T. Hayward-Schneider; D. Coster; A. Bergmann; M. Murugappan; S. Brunner; L. Villard; F. Jenko (Computer Physics Communications, 2024)

Efficient injection of gas tracers into rivers: A tool to study Surface water–Groundwater interactions - Théo Blanc; Morgan Peel; Matthias S. Brennwald; Rolf Kipfer; Philip Brunner (Water Research, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Climatic shifts threaten alpine mycorrhizal communities above the treeline - R. Arraiano-Castilho; M.I. Bidartondo; T. Niskanen; I. Brunner; S. Zimmermann; B. Senn-Irlet; B. Frey; U. Peintner; T. Mrak; L.M. Suz (Fungal Ecology, 2024)

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

Forestry in the Face of Global Change: Results of a Global Survey of Professionals - Austin Himes; Jürgen Bauhus; Shankar Adhikari; Saroj Kanta Barik; Hugh Brown; Andreas Brunner; Philip J. Burton; Lluís Coll; Anthony W. D’Amato; Jurij Diaci; Yonten Dorji; Ernest G. Foli; et al. (Current Forestry Reports, 2023)
Purpose of Review Forests support most global terrestrial biodiversity and contribute to the livelihood of billions of people, but these and other benefits are in jeopardy due to global change. This leads to questions, such as how to address the challenges of global change in forest management, given the lack of knowledge and deep uncertainty about future developments. In addition, many of the impediments to implement adaptation strategies are unknown. Recent Findings Here, we present an overview of results from a global survey of 754 forestry professionals (370 researchers and educators, 227 practicing foresters, 37 policymakers, 64 administrators, and 56 with other or unspecified roles) from 61 countries across 6 continents who were interested in global change issues. These professionals were asked about their opinion regarding three different adaptation strategies: resist , adapt , and transform . Most respondents agreed that the majority of global change factors will negatively influence the ability of forests to provide desired ecosystem services. Similarly, they agreed about major challenges when implementing adaptation strategies and specifically whether our current knowledge base is sufficient. These concerns were not limited to ecological aspects, but respondents also highlighted the need for a better appreciation of social/political and economic barriers, especially regarding transformation strategies. In addition, the response patterns, including differences due to economic status, highlight the importance of developing and evaluating adaptation strategies in a local social–ecological context. Summary Our study demonstrates a widespread perception on the part of forestry professionals around the world, especially among researchers and practitioners, that many global change factors will affect sustainable forest management negatively, resulting in the need for active silvicultural adaption. The results also suggest potential barriers to different adaptation strategies, particularly a relative lack of information and social acceptance for transform strategies. Further, this study highlights the importance of social and political factors and the need to understand the general public’s values regarding adaptation strategies as well as how the influence of public opinion is perceived by forest managers.

Protective role of the placental efflux transporter BCRP/ABCG2 in the relationship between prenatal cadmium exposure, placenta weight, and size at birth - Emily S. Barrett; Zorimar Rivera-Núñez; Kylie Getz; Pamela Ohman-Strickland; Ranran Zhang; Danielle Kozlosky; Cathleen L. Doherty; Brian T. Buckley; Jessica Brunner; Richard K. Miller; Thomas G. O'Connor; Lauren M. Aleksunes (Environmental Research, 2023)

Prenatal perfluoroalkyl substances exposure and maternal sex steroid hormones across pregnancy - Zorimar Rivera-Núñez; Carolyn W. Kinkade; Leena Khoury; Jessica Brunner; Hannah Murphy; Christina Wang; Kurunthachalam Kannan; Richard K. Miller; Thomas G. O'Connor; Emily S. Barrett (Environmental Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

An experimental test of how parasites of predators can influence trophic cascades and ecosystem functioning - Jaime M. Anaya‐Rojas; Rebecca J. Best; Franziska S. Brunner; Christophe Eizaguirre; Miguel Costa Leal; Carlos J. Melián; Ole Seehausen; Blake Matthews (Ecology, 2019)
Parasites can shape the structure and function of ecosystems by influencing both the density and traits of their hosts. Such changes in ecosystems are particularly likely when the host is a predator that mediates the dynamics of trophic cascades. Here, we experimentally tested how parasite load of a small predatory fish, the threespine stickleback, can affect the occurrence and strength of trophic cascades and ecosystem functioning. In a factorial mesocosm experiment, we manipulated the density of stickleback (low vs. high), and the level of parasite load (natural vs. reduced). In addition, we used two stickleback populations from different lineages: an eastern European lineage with a more pelagic phenotype (Lake Constance) and a western European lineage with a more benthic phenotype (Lake Geneva). We found that stickleback caused trophic cascades in the pelagic but not the benthic food chain. Evidence for pelagic trophic cascades was stronger in treatments where parasite load of stickleback was reduced with an antihelmintic medication, and where fish originated from Lake Constance (i.e., the more pelagic lineage). A structural equation model revealed that differences in stickleback lineage and parasite load were most likely to impact trophic cascades via changes in the composition, rather than overall biomass, of zooplankton communities. Overall, our results provide experimental evidence that parasites of predators can influence the cascading effects of fish on lower trophic levels with consequences on ecosystem functioning.

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Seasonal dynamics and potential drivers of ranavirus epidemics in wood frog populations - Emily M. Hall; C. S. Goldberg; J. L. Brunner; E. J. Crespi (Oecologia, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

A tapetal ablation transgene induces stable male sterility and slows field growth in Populus - Estefania Elorriaga; Richard Meilan; Cathleen Ma; Jeffrey S. Skinner; Elizabeth Etherington; Amy Brunner; Steven H. Strauss (Tree Genetics & Genomes, 2014)

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses - Coleen C. Suckling; Melody S. Clark; Christine Beveridge; Lars Brunner; Adam D. Hughes; Elizabeth M. Harper; Elizabeth J. Cook; Andrew J. Davies; Lloyd S. Peck (Invertebrate Reproduction & Development, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Gradenbach Observatory—monitoring deep-seated gravitational slope deformation by geodetic, hydrological, and seismological methods - E. Brückl; F. K. Brunner; E. Lang; S. Mertl; M. Müller; U. Stary (Landslides, 2013)

More breast cancer patients prefer BRCA-mutation testing without prior face-to-face genetic counseling - Aisha S. Sie; Wendy A. G. van Zelst-Stams; Liesbeth Spruijt; Arjen R. Mensenkamp; Marjolijn J. L. Ligtenberg; Han G. Brunner; Judith B. Prins; Nicoline Hoogerbrugge (Familial Cancer, 2013)

Fine-root turnover rates of European forests revisited: an analysis of data from sequential coring and ingrowth cores - I. Brunner; M. R. Bakker; R. G. Björk; Y. Hirano; M. Lukac; X. Aranda; I. Børja; T. D. Eldhuset; H. S. Helmisaari; C. Jourdan; B. Konôpka; B. C. López; et al. (Plant and Soil, 2013)

Genes with expression levels correlating to drip loss prove association of their polymorphism with water holding capacity of pork - R. M. Brunner; T. Srikanchai; E. Murani; K. Wimmers; S. Ponsuksili (Molecular Biology Reports, 2012)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Efficient and stable transgene suppression via RNAi in field-grown poplars - Jingyi Li; Amy M. Brunner; Olga Shevchenko; Richard Meilan; Cathleen Ma; Jeffrey S. Skinner; Steven H. Strauss (Transgenic Research, 2008)

Variation in fine root biomass of three European tree species: Beech ( Fagus sylvatica L.), Norway spruce ( Picea abies L. Karst.), and Scots pine ( Pinus sylvestris L.) - L. Finér; H.-S. Helmisaari; K. Lõhmus; H. Majdi; I. Brunner; I. Børja; T. Eldhuset; D. Godbold; T. Grebenc; B. Konôpka; H. Kraigher; M.-R. Möttönen; et al. (Plant Biosystems, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Alcohol-inducible gene expression in transgenic Populus - S. A. Filichkin; R. Meilan; V. B. Busov; C. Ma; A. M. Brunner; S. H. Strauss (Plant Cell Reports, 2006)

A gis-based assessment on the vulnerability and future extent of the tropical forests of the congo basin - Quanfa Zhang; Christopher O. Justice; Mingxi Jiang; Jake Brunner; David S. Wilkie (Environmental Monitoring and Assessment, 2006)

A novel D458V mutation in the SANS PDZ binding motif causes atypical Usher syndrome - E. Kalay; A. P. M. de Brouwer; R. Caylan; S. B. Nabuurs; B. Wollnik; A. Karaguzel; J. G. A. M. Heister; H. Erdol; F. P. M. Cremers; C. W. R. J. Cremers; H. G. Brunner; H. Kremer (Journal of Molecular Medicine, 2005)

6-Alkylsalicylic Acids and 6-Alkylresorcylic Acids from Ants in the Genus Crematogaster from Brunei - T. H. JONES; S. R. BRUNNER; A. A. EDWARDS; D. W. DAVIDSON; R. R. SNELLING (Journal of Chemical Ecology, 2005)

Wood-ash recycling affects forest soil and tree fine-root chemistry and reverses soil acidification - I. Brunner; S. Zimmermann; A. Zingg; P. Blaser (Plant and Soil, 2004)

Fine root growth and element concentrations of Norway spruce as affected by wood ash and liquid fertilisation - M. Genenger; S. Zimmermann; D. Hallenbarter; W. Landolt; E. Frossard; I. Brunner (Plant and Soil, 2003)

Special Contribution: BOHEMA 2001-2003: Passive Seismic Experiment to Study Lithosphere-Asthenosphere System in the Western Part of the Bohemian Massif - J. Plomerová; U. Achauer; V. Babuška; M. Granet; U. Achauer; V. Babu.Ka; A. Boušková; K. Bräuer; M. Brož; M. Brunner; T. Fischer; S. Funke; et al. (Studia Geophysica et Geodaetica, 2003)

Molecular identification of fine roots of trees from the Alps: reliable and fast DNA extraction and PCR–RFLP analyses of plastid DNA - I. Brunner; S. Brodbeck; U. BÜchler; C. Sperisen (Molecular Ecology, 2001)
Fine roots of trees are intensively used as indicators to assess soil alterations, e.g. those owing to atmospheric inputs of acidifying substances, but their identification to species with morphological criteria is difficult. In this study, we established molecular techniques in order to identify fine roots of the 30 most common tree species of the Alps. We developed a protocol for efficient isolation of DNA from fine roots with extraction of DNA in the presence of polyvinylpyrrolidone (PVP) and polyvinylpolypyrrolidone (PVPP). The trn L (UAA) intron of plastid DNA was used as a marker for fine root identification. We amplified and sequenced this intron with plant universal primers. The size of the sequences ranged from 444 to 672 bp . A synoptic key for species identification was designed on the basis of restriction fragment patterns predicted from sequence data. Using the restriction enzyme Taq I as key enzyme, and where necessary Hin fI, Rsa I and Cfo I, 16 taxa, including Picea abies , Larix decidua , Abies alba , and Fagus sylvatica , the dominant tree species of the Alpine region could be identified by agarose gel electrophoresis of restriction fragments. Fourteen taxa could be identified to the genus level, among them Quercus , Salix and Populus species. In a field study, conducted in a 20 × 30 m plot of a mixed forest with five tree species, fine roots of 43 out of 46 samples were identified and their distributions were mapped. These results demonstrate the utility of our DNA extraction method and of the trn L intron for the identification of fine tree roots.

Molecular mapping of the Rph7.g leaf rust resistance gene in barley (Hordeum vulgare L.) - S. Brunner; B. Keller; C. Feuillet (Theoretical and Applied Genetics, 2000)

High 5HT 2A receptor occupancy in M100907-treated schizophrenic patients - M. Talvik-Lotfi; S. Nyberg; A. -L. Nordström; H. Ito; C. Halldin; F. Brunner; L. Farde (Psychopharmacology, 2000)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

Exchange of colicin receptor capacity between strains of Escherichia coli sensitive or resistant to colicin K-K235 - David P. Brunner; Gary S. Graham; Ronald W. Treick (Archives of Microbiology, 1982)